COVID-19 Pneumonia Pneumomediastinum. Clinical Cases - N. А. Lesteva; E. V. Аdieva; S. S. Lesina; M. I. Аibazova; K. B. Аbramov; K. I. Sebelev; А. N. Kondratiev (Вестник анестезиологии и реаниматологии)
Spontaneous pneumomediastinum is a rare complication of viral pneumonia. The prevalence of pneumomediastinum among coronavirus infection patients is unknown.Subjects and methods. Three cases of spontaneous pneumomediastinum among the COVID-19 pneumonia patients were analyzed. The researchers investigated and compared clinical, radiological and laboratory data.Results. According to the research results, no correlation was found between the development of pneumomediastinum and changes in values of blood laboratory tests. As well as there were no signs of correlation between drug treatment and pneumomediastinum frequency.Conclusion: The researchers suggest that the leading cause of spontaneous pneumomediastinum is viral pneumonia-associated severe alveolar damage.